Cork oak afforestation using innovative techniques to mitigate climate change - Camilo-Alves, Constança (2024)
Cork oak (Quercus suber) woodlands are distributed across the western Mediterranean. Renowned for their cork, their most iconic product is the stopper, essential for the wine industry. Cork is also extensively used in civil construction, aerospace, and sports industries. The renewable nature of cork allows harvesting every 9 to 10 years, with trees living for approximately two centuries and being debarked up to 17 times. However, cork oak woodlands face severe threats. Widespread cork oak mortality events have been occurring since the 1990s. Initially attributed to root disease caused by the oomycete Phytophthora cinnamomi, subsequent research suggests that multiple factors acting synergistically contribute to the decline (Camilo-Alves et al. 2013). These factors include drought events, soil constraints on root development, and improper management practices. Though the cork oak distribution area has remained relatively stable, tree loss has resulted in a steady reduction of canopy cover. Furthermore, an alarming decline in tree regeneration has been occurring, compromising the sustainability of these ecosystems. Faced with this situation, particularly the predicted cork shortage in the near future, the cork sector is collaborating with the scientific community to find solutions to promote tree regeneration, survival, vitality, and productivity.